Endpoint Detection Based on Optical Method in Chemical Mechanical Polishing - Tian, Fangxin; Wang, Tongqing; Lu, Xinchun (Micromachines (Basel), 2023)
Endpoint detection is an important technology in chemical mechanical polishing (CMP), which is used to capture the material interface and compensate the variations of consumables and incoming wafer thickness. This paper aimed to apply optical detection in metal CMP. An in situ optical measurement system was developed for a 12-inch CMP tool. Kinematic analysis of the scanning trajectory of the laser device indicated the relative position relationship between the device and the wafer. Average optical data within the wafer described the material removal of metal CMP. Furthermore, optical data and location described the non-uniformity of the entire wafer surface. In this research, the polishing condition and the residual of the wafer edge are characterized by optical trace. Pauta Criterion is used to discriminate the inflexion point of the material interface. The results reveal that the interface capture is accurate and effective.